Targeted synthetic pharmacotherapy for psoriatic arthritis: state of the art. (2nd May 2020) - Caso, Francesco; Navarini, Luca; Ruscitti, Piero; Chimenti, Maria Sole; Girolimetto, Nicolò; Del Puente, Antonio; Giacomelli, Roberto; Scarpa, Raffaele; Costa, Luisa
ABSTRACT: Introduction: In recent years, different studies regarding psoriatic arthritis (PsA) have shown the pathogenetic role of dysfunction of signaling pathways involving the phosphodiesterase-4 enzyme and transcription factors or enzymes belonging to the kinase (JAK)–signal family pathway. These also represent the target of several drugs known as targeted synthetic disease-modifying antirheumatic drugs (tsDMARDs). Areas covered: The authors performed a systematic literature search using the PubMed database, as well as through retrieving data from randomized controlled trials, their post-hoc analysis, and pooled data analysis on the efficacy and safety profile of the PDE4 inhibitor (PDE4i), apremilast, and the inhibitors of JAK (JAKis), tofacitinib, filgotinib, baricitinib, and upadacitinib, in PsA. Expert opinion: In PsA, the PDE4i, apremilast, and the JAKi, tofacitinib, are effective across multiple clinical domains and have an acceptable tolerability profile, thus expanding the treatment options available for PsA patients. Apremilast and tofacitinib show several advantages mainly represented by their oral administration, a fast onset of action, and a short half-life. Data on tsDMARDs in PsA are still limited, and randomized trials and real-life studies are advocated.